HLA antigens in severe pre-eclampsia. - Redman, C; Bodmer, J; Bodmer, W; Beilin, L; Bonnar, J (1978)
When the HLA types of 80 pre-eclamptic women and their husbands and 83 control couples were compared significantly more pre-eclamptic women had only one identifiable HLA B antigen, and were presumed to be homozygous at this locus. Those who were homozygous for HLA B were more likely to be homozygous for HLA A as well, and more likely to be homozygous for HLA A as well, and to have more severe pre-eclampsia. There was neither increased HLA incompatibility nor greater antigen-sharing between pre-eclamptic women and their husbands, but maternal HLA A and B homozygosity reduced the number of antigenic disparities between pre-eclamptic women and their husbands. The data are consistent with the hypothesis that maternal recessive immune-response genes may contribute to the development of pre-eclampsia. Alternatively maternal HLA homozygosity may predispose to fetal changes comparable to runting.